2022
DOI: 10.1093/advances/nmac065
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ketogenic Diets in Multiple Sclerosis and Related Animal Models: An Updated Review

Abstract: Prescribing a ketogenic diet (KD) is a century-old dietary intervention mainly used in the context of intractable epilepsy. The classic KD and its variants regained popularity in recent decades, and they are considered potentially beneficial in a variety of neurological conditions other than epilepsy. Many patients with multiple sclerosis have attempted diet modification for better control of their disease, whereas evidence thus far remains insufficient to recommend a specific diet for these patients. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…Kim et al (2012) showed the favorable effect of KD correlated with decreased inflammation markers of brain in an experimental autoimmune encephalomyelitis (EAE) murine model [119]. KD could rescript crucial characteristics of MS pathogenesis through enriched CNS bioenergetics, and ketosis supported the expression of antioxidant pathways and lowered effector cell related protection [123]. KD is allied with a neuroprotective activity imparted by an enhanced sirtuin 1, (SIRT1-a participant of class III HDACs), expression in numerous cell types in the CNS [124][125][126].…”
Section: Ketogenic Diet Mediated Immune Modulation In Central Nervous...mentioning
confidence: 98%
“…Kim et al (2012) showed the favorable effect of KD correlated with decreased inflammation markers of brain in an experimental autoimmune encephalomyelitis (EAE) murine model [119]. KD could rescript crucial characteristics of MS pathogenesis through enriched CNS bioenergetics, and ketosis supported the expression of antioxidant pathways and lowered effector cell related protection [123]. KD is allied with a neuroprotective activity imparted by an enhanced sirtuin 1, (SIRT1-a participant of class III HDACs), expression in numerous cell types in the CNS [124][125][126].…”
Section: Ketogenic Diet Mediated Immune Modulation In Central Nervous...mentioning
confidence: 98%
“…Currently, a body of objective evidence that suggests a potentially favourable effect of the ketogenic diet in the treatment of MS is available. It can affect the course and prophylaxis of the disease while simultaneously offering safety of use and feasibility [ 201 ]. Taking into account the demyelination processes observed in MS, an effect of the ketogenic diet is suggested for the possible reconstruction and repair of the myelin sheaths.…”
Section: The Role Of the Ketogenic Diet In The Therapy Of Multiple Sc...mentioning
confidence: 99%
“…Our MR analysis supports the causal roles of these metabolites in the development of MS. Notably, the higher circulating levels of ketone bodies (i.e., acetoacetate and acetone) may reflect a protective shift in energy metabolism in MS patients, and ketogenic diets have shown suggestive benefits for MS patients 43 . It is of great interest to investigate the roles of ketone bodies in the development of MS, in addition to its treatment.…”
Section: Discussionmentioning
confidence: 99%